Contribuições para otimização estrutural de torres tubulares de aço para turbinas eólicas - Lima, João Baptista Cardoso Athayde (2011)
The main subjects of the globalized world have passed necessarily by issues related to sustainability, clean energy, environment exploration in an ecologically correct way, and technology innovation to maintain a healthy planet. In this context, the wind has been highlighting, especially in the Northeast of Brazil, because of the large wind potential and the characteristics of renewability and complementarily with hydropower energy. The towers represent significant portion of the cost of the system, tends to grow seeking greatest wind speeds and allowing the use of wind turbines with bigger production capacity, emphasizing its importance as a structural element of the system. The main objective of this work is to formulate an optimization model of tubular steel towers, composed of segments in truncated cone. The aim is a minimum weight solution, having outer diameters and plate thicknesses characteristics of each segment as design variables. Constraints related to strength, stability and stiffness are imposed based on Brazilian codes. Constraints related to natural frequency, the limitations of transport and geometry are also required. The nacelle/rotor conjunct is modeled as a rigid mass attached to the top of the tower, without rotation, and the loading acting on the structure includes the weights of the tower and the nacelle/rotor conjunct, the static wind effect on the tower and on rotor blades. The analysis model adopts cantilever beam and employs a formulation for geometric nonlinear finite element method using a C++ program. The optimization model was implemented in MATLAB and due to the discrete nature of the design variables and the discontinuities of the constraint functions and their gradients we use genetic algorithms in the solution. Searches in the neighborhood of the discrete solutions are performed using a gradient based algorithm (fmincon in MATLAB). Applications to several tower heights are made, including comparisons with a cylindrical tower to validate the model. The results are analyzed against others models in the literature. The concepts of rigid and flexible tower project are discussed relaxing their stiffness and frequency constraints. Solutions obtained are analyzed using shell elements of ABAQUS analysis program to check tensions and displacements.